Molecular and genetic characterization of the Ry adg locus on chromosome XI from Andigena potatoes conferring extreme resistance to potato virus Y - Herrera, M.R.; Jara Vidalon, L.; Montenegro, J.D.; Riccio, C.; Guzmán, F.; Bartolini, I.; Ghislain, M. (Springer, 2018)
Potato virus Y (PVY) is causing yield and quality losses forcing farmers to renew periodically their seeds from clean stocks. Two loci for extreme resistance to PVY, one on chromosome XI and the other on XII, have been identified and used in breeding. The latter corresponds to a well-known source of resistance (Solanum stoloniferum), whereas the one on chromosome XI was reported from S. stoloniferum and S. tuberosum group Andigena as well. To elucidate its taxonomic origin in our breeding lines, we analyzed the nucleotide sequences of tightly linked markers (M45, M6) and screened 251 landraces of S. tuberosum group Andigena for the presence of this gene. Our results indicate that the PVY resistance allele on chromosome XI in our breeding lines originated from S. tuberosum group Andigena. We have developed two marker assays to accelerate the introgression of Ryadg gene into breeding lines by marker-assisted selection (MAS). First, we have multiplexed RYSC3, M6 and M45 DNA markers flanking the Ryadg gene and validated it on potato varieties with known presence/absence of the Ryadg gene and a progeny of 6,521 individuals. Secondly, we developed an allele-dosage assay particularly useful to identify multiplex Ryadg progenitors. The assay based on high-resolution melting analysis at the M6 marker confirmed Ryadg plex level as nulliplex, simplex and duplex progenitors and few triplex progenies. These marker assays have been validated and can be used to facilitate MAS in potato breeding.